2003
DOI: 10.1007/s00421-002-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-exercise ingestion of differing amounts of carbohydrate on subsequent metabolism and cycling performance

Abstract: Studies on the effect of the pre-exercise ingestion of carbohydrate on metabolism and performance have produced conflicting results, perhaps because of differences in the designs of the studies. The purpose of the present study was to examine the effects of ingesting differing amounts of glucose pre-exercise on the glucose and insulin responses during exercise and on time-trial (TT) performance. Nine well-trained male cyclists completed four exercise trials separated by at least 3 days. At 45 min before the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 47 publications
7
61
0
2
Order By: Relevance
“…The latter is in agreement with (22,43) and also in contrast with previous literature (28,41). The variation in time to exhaustion within conditions was relatively large (CV: placebo 25.4%, Glu 13.3%, Gal 14.8%), which may explain why there are no significant differences from the placebo condition for either CHO condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The latter is in agreement with (22,43) and also in contrast with previous literature (28,41). The variation in time to exhaustion within conditions was relatively large (CV: placebo 25.4%, Glu 13.3%, Gal 14.8%), which may explain why there are no significant differences from the placebo condition for either CHO condition.…”
Section: Discussionsupporting
confidence: 93%
“…These transient metabolic disturbances, at the start of exercise, as well as mechanisms that increase glycogen utilisation (6,17), may explain why pre-exercise glucose does not always provide an additional benefit in comparison to placebo. Regardless, there now appears to be less concern about the efficacy and use of simple sugars in the hour prior to exercise (18,22,26) despite early reservations regarding rebound hypoglycaemia (6,15). If rebound hypoglycaemia is relevant to endurance performance the use of other forms of CHO, such as galactose, with a low glycaemic index (GI: ~20), which has no primary insulin drive (37), may overcome the issue.…”
Section: Introductionmentioning
confidence: 99%
“…Replenishing carbohydrates during exercise maintains or increases the body's carbohydrate oxidation rate [11], maintains the blood glucose level [12], helps reduce the rate of perceived exertion [13], and slows glycogenolysis in the liver [14] and muscles [15], thus delaying the onset of fatigue during exercise [11]. It has also been reported that consuming additional carbohydrates after exercise increases muscle glycogen synthesis and is thus positively correlated with glycogen retention per hour during recovery [16].…”
Section: Introductionmentioning
confidence: 99%
“…7 Research on the impact of pre-exercise nutrition on performance, especially within an hour prior to exercise, remains controversial. 14 Studies have shown increases, 11,17,22,24,25 no effect, 4,7,8,13,23 or even decreases in performance 10,14 after CHO ingestion within the hour prior to exercise. More recently, researchers have begun manipulating the timing of pre-exercise nutrition to determine the effects on subsequent exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…19 The majority of pre-exercise nutritional studies have examined carbohydrate-only administration in liquid form, and its subsequent effect on steady-state endurance cycling performance. 12,14 However, a liquid carbohydrate drink may not be representative of all pre-exercise nutritional practices, since many athletes may choose to consume a solid meal or energy bar and not necessarily a liquid carbohydrate drink. Many of these energy bars are marketed as nutritional fuel support for exercise, and are accompanied by suggestions for consumption before, during, and after exercise.…”
Section: Introductionmentioning
confidence: 99%